Civil resistance : comparative perspectives on nonviolent struggle - Schock, Kurt, 1963- (Social movements, protest, and contention, 2015)
In the past quarter century the world has witnessed dramatic social and political transformations, due in part to an upsurge in civil resistance. There have been significant uprisings around the globe, including the toppling of communist regimes in Eastern Europe, the Color Revolutions, the Arab Spring, protests against war and economic inequality, countless struggles against corruption, and demands for more equitable distribution of land. These actions have attracted substantial scholarly attention, reflected in the growth of literature on social movements and revolution as well as literature on nonviolent resistance. Until now, however, the two bodies of literature have largely developed in parallel-with relatively little acknowledgment of the existence of the other. In this useful collection, an international and interdisciplinary group of scholars takes stock of the current state of the theoretical and empirical literature on civil resistance. Contributors analyze key processes of nonviolent struggle and identify both frictions and points of synthesis between the narrower literature on civil resistance and the broader literature on social movements and revolution. By doing so, Civil Resistance: Comparative Perspectives on Nonviolent Struggle pushes the boundaries of the study of civil resistance and generates social scientific knowledge that will be helpful for all scholars and activists concerned with democracy, human rights, and social justice.